Implementasi Software Berhitung Berbasis Android di Taman Kanak-kanak Kecamatan Jagakarsa - Naely Farkhatin (Universitas Indraprasta PGRI Jakarta, 2018)
In principle, the development of information technology helps people to interact with others or surroundings. Further, with the change in technology providing simpler, more collaborative and more transparent communication and computer system to many people, it is also important for children to have skill in computer that they can learn effectively. Counting skill has been introduced to kindergarten, creating various counting methods to help teachers and parents to teach it. However, the methods will not be effective without the use of application system in a learning process because every student is unique that he needs different way of learning. A more decisive matter is the parent’s understanding about how the children learn and what their way of learning is. Based on the description above, it is necessary to provide a learning media in the form of application which can draw children’s interest and facilitate children’s learning process with a play-based learning concept applied beyond the formal learning time in which this media can be flexibly used. This research is conducted by applying android-based counting software at kindergarten in Jagakarsa.